2022
DOI: 10.1186/s12882-022-02723-9
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported gastrointestinal symptoms in patients with peritoneal dialysis: the prevalence, influence factors and association with quality of life

Abstract: Background The aims of this study were to investigate the prevalence and the influence factors of gastrointestinal symptoms, and its association with the quality of life (QOL) in peritoneal dialysis (PD) patients. Methods Continuous ambulatory PD patients (CAPD) who followed up in our PD center between March 2016 and December 2017 were enrolled in this cross-sectional study. Gastrointestinal symptom rating scale (GSRS) was used to evaluate gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Most patients receiving PD experience gastrointestinal symptoms, including constipation (14.2–0.3%), indigestion (32.7%), early satiety (41.6%) and gastroesophageal reflux (30.7–93.1%) 117 . Compared with patients receiving HD, constipation is less common among patients treated with PD owing to higher dietary fibre and potassium intake, more liberal fluid consumption, more active lifestyle and lower use of phosphate binders and ion exchange resins 118 120 . Nonetheless, constipation is associated with higher risks of catheter malfunction, peritonitis and technique failure, which demands a proactive treatment approach 118 .…”
Section: Global Patient-reported Pd Outcomesmentioning
confidence: 99%
“…Most patients receiving PD experience gastrointestinal symptoms, including constipation (14.2–0.3%), indigestion (32.7%), early satiety (41.6%) and gastroesophageal reflux (30.7–93.1%) 117 . Compared with patients receiving HD, constipation is less common among patients treated with PD owing to higher dietary fibre and potassium intake, more liberal fluid consumption, more active lifestyle and lower use of phosphate binders and ion exchange resins 118 120 . Nonetheless, constipation is associated with higher risks of catheter malfunction, peritonitis and technique failure, which demands a proactive treatment approach 118 .…”
Section: Global Patient-reported Pd Outcomesmentioning
confidence: 99%
“…In the current study, we investigated various measures of constipation and their relationship with QoL in an Australian cohort of PwP and found that sufering from constipation was signifcantly associated with a reduced QoL as measured with the PDQ-39 instrument. We went on to further explore the relationship between other gastrointestinal symptoms and QoL using the comprehensive Gastrointestinal Symptom Rating Scale (GSRS), which has previously been used to evaluate the frequency and severity of gastrointestinal symptoms in assorted clinical settings [32,[34][35][36][37][38][39][40][41][42][43][44][45], but not in a QoL study in PwP. Our fndings confrmed that, in addition to constipation and other symptoms of gastrointestinal hypomotility, a number of other gastrointestinal symptoms that are not included in current clinical assessment protocols also had a negative impact on QoL.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,27,28 The risk factors associated with the severity of GI symptoms include higher glycosylated haemoglobin, higher depression score, higher daily pill intake, lower urine output and lower diastolic blood pressure. 27 In addition, higher dyspepsia and eating dysfunction scores have been found to be independently associated with lower scores on the physical component scale and QOL. 27 In this systematic review, nausea and diarrhoea were reported as the main outcomes in 27 (44%) and 26 (43%) trials, respectively, followed by vomiting in 22 (36%) trials, constipation in 21 (34%) trials and abdominal pain in 19 (31%) trials.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the accompanying physical distress, GI symptoms are also associated with psychosomatic problems such as anxiety, headache, insomnia, depression and poor QOL in patients receiving dialysis. 19,20,27,28 Furthermore, GI symptoms have been reported to be negatively associated with psychosocial well-being in kidney failure patients. Dyspepsia, eating dysfunction and constipation are independently associated with depression and worse physical well-being and QOL in dialysis patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation